Analisis rasio keuangan untuk mengukur kinerja keuangan pada PT. Telkom Indonesia (Persero) Tbk yang terdaftar di Bursa Efek Indonesia tahun 2019- 2022 - Dominggus, Ester Alfrida; Kalangi, Lintje; Kapojos, Peter M. (Yayasan Widyantara Nawasena Raharja, 2025)
The objective of this research is to ascertain the financial performance of PT Telkom Indonesia, a company listed on the Indonesian Stock Exchange. This research is qualitative and descriptive in nature, utilizing both qualitative and quantitative data. The secondary data source was used as the research basis. The research findings from 2019 to 2022 clearly indicate that the financial performance, measured using liquidity, solvency, activity and growth ratios, is poor. Conversely, financial performance measurement based on profitability ratios, such as the net profit margin ratio, demonstrates favorable outcomes, while return on equity falls short. The activity ratio, measured by receivable turnover, shows positive results, contrasting with the less favorable performance of total asset turnover.